Instructional Design for Reading Comprehension Teaching Materials - Mulat, Astuti; Sudarsono, Sudarsono; Salam, Urai (International Journal of Learning and Instruction (IJLI), 2024)
The study aimed to design instructional material for teaching reading comprehension to year ten students at Madrasah Aliyah Khulafaur Rasyidin. This research took the form of development research. The method used in this research was design and development research. As a procedure, the researcher used the ADDIE. However, due to time limitations, the researcher only implemented three phases in this study: analyzing, designing, and developing (ADD). In the analyzing phase, the researcher interviewed the English teacher to determine the actual conditions of the students, the teacher, and the school. In the designing phase, the researcher observed the textbook and the curriculum applied in the school to design the teaching material that meets the teacher"™s and student"™s needs. In the development phase, all drafts in the previous phase were made into a teacher's book and organized using Canva. Then, the researcher used internal evaluation to validate the product. After the researcher finished the product, it was given to the English teacher in the target school. In conclusion, the instructional design is useful for teaching reading comprehension to year-10 students of Madrasah Aliyah Khulafaur Rasyidin.  Keywords: Instructional Design, Teaching Material, Reading Comprehension, Narrative Text